O JORNALISMO CONTEMPORÂNEO E A MULHER JORNALISTA Um estudo sobre gênero dentro da profissão no estado de São Paulo São Bernardo - MATEOS, JÉSSICA DE OLIVEIRA COLLADO (2019)
Taking into account the scenario of crisis and structural changes in journalism and the growing female majority in the professional body, this research has as main objective to investigate how the discriminatory processes suffered by women journalists in this context of transformations are configured. The hypothesis is that the journalist suffers from a double embryo: the first because she is a woman and the second due to the crisis. The theoretical references that support these affirmations revolve around the imaginary, the discrimination of gender and contemporary journalism. One of the authors used is Martín Sagrera, who points out the appropriation of the myth by institutions; Pierre Bourdieu, Gilles Lipovetsky and Naomi Wolf, who, among others, bring the discussion about discrimination against women and chauvinism into the social imaginary. Constância Lima Duarte and Dulcília Buitoni tell in depth interviews the history of the struggle for women's rights present in the feminist and women's press, the women's trajectory to enter the profession and how the woman is portrayed by the media in Brazil, an unreal body-product; And the third interviewee, the researcher Cláudia Nonato, explains the changes in the world of the journalist's work. There are also Roseli Figaro and Chris Anderson, Emily Bell and Clay Shirky, respectively, who report on the changes in the world of work, the crisis of the business model and the restructuring of journalism. In addition to the bibliographic research, the study uses in-depth interviews with female expert researchers and a quantitative and qualitative survey applied in two phases through online questionnaires to women journalists over 18 who work in the State of São Paulo. The answers of the questionnaires were categorized and analyzed in light of the theme concepts, the interviews and previous studies carried out by the author of this dissertation. It has been demonstrated that structures of sexual domination are still strongly present in the journalistic environment, revealing a noxious atmosphere and the urgency of implementing effective measures of awareness and punishment in the workplace so that a less sexist and safer journalistic culture can be found.